Intellectuals and Civil Society in the Middle East : Liberalism, Modernity and Political Discourse. - Bamyeh, Mohammed A. (I.B. Tauris & Company, Limited, 2012)
"After the 1989 Islamist coup in Sudan, the National Islamic Front under General Omar al-Bashir and Dr. Hasan Turabi attempted to institutionalise, codify and implement Shari'a law throughout the country. However, by 2005, with the signing of the Comprehensive Peace Agreement ending 22 years of civil war, the government agreed to halt its policy of Islamisation in the South. Shari'a and Islamism in Sudan explores how Sudanese society has been transformed by this period of implementation of Islamic Law, and furthermore asks, what are the continuing effects of this policy? And what are the implications of the Peace Agreement for the future of Islamist politics in Sudan and of the country? With data drawn from Carolyn Fluehr-Lobban's most recent research in the region, this book is a vital and unique examination of the nature of the Sudanese state and society, offering invaluable insight for all those interested in the politics, society, and the future of Sudan and the nature of political Islam."--Bloomsbury publishing.